KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS VIII MTs ISLAMIYAH MEDAN MELALUI PENDEKATAN OPEN-ENDED - Ade Evi Fatimah (MES: Journal of Mathematics Education and Science, 2019)
Abstract. This research is a Classroom Action Research which aims to improve the mathematical reasoning ability of students of class VIII Mts Islamiyah Medan through the Open-Ended approach. The subjects in this study were all students of class VIII-1 MTs Islamiyah Medan, totaling 24 students. This research was conducted in 2 cycles, namely cycle I and II, each of which consisted of two meetings. The instruments used in this study were observation guidelines for implementing learning with the Open-Ended approach, cycle tests to measure students' mathematical reasoning abilities towards learning mathematics with the Open-Ended approach, interview guidelines and documentation. Data from observations, tests, and questionnaires were analyzed quantitatively which was strengthened by the results of interviews and descriptive qualitative documentation. The results showed that the mathematical reasoning ability of students in class VIII-1 MTs Islamiyah Medan increased from cycle I to cycle II after learning was carried out with the Open-Ended approach. This is shown by as many as 20 students or 83.3% experienced an increase in mathematical reasoning ability based on the total score of aspects of mathematical reasoning ability. The average percentage of test scores increased from 66.6% in the first cycle to 83.3% in the second cycle and in the high category. Based on observations of the implementation of learning with the Open-Ended approach is good and in accordance with the characteristics of the Open-Ended Approach. Based on the results of interviews and questionnaire results data student responses to mathematics learning in relation to mathematical reasoning abilities, increased from cycle I to cycle II.Keywords: Mathematical Reasoning Ability, Open-Ended Approach.